Materialisme Sebagai Penghambat Pembangunan Kesejateraan Sosial - Mohammad Sabiq; Akhmad Jayadi; Imam Nawawi; Mohammad Wasil (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2019)
Materialism and sich are the driving spirit of the community in achieving economic and financial security that saves a holistic and socially just welfare. This can be seen from the lives of people in materialistic developed countries, where the level of social stress is higher, economic inequality widens, horizontal conflict is rife. This research uses Pierre Felix Bourdieu's social theory in seeing people trust the expenditure of material with other values, such as spiritual and cultural values ​​that are no less urgent as elements of social welfare development. This study found that materialism on the one hand has a positive effect, where people are encouraged to use material standards in measuring the level of welfare they expect. On the other hand, materialism closes the presence of values ​​such as spirituality, local wisdom and agriculture in completing more holistic welfare standards.